(untitled) (Journal of Laboratory Animal Science, 2018)
Science is a global enterprise, as illustrated by the number and scope of international research collaborations and scientific meetings, as well as the number of journals publishing articles from the international scientific community. As institutions seek to compete on the global market it is critical to ensure an internationally accepted level of animal care and welfare is maintained by institutions using animals for research, testing and education. AAALAC International’s accreditation program utilizes the flexibility of performance standards; is sensitive to differing legal and cultural issues; promotes the “cross fertilization” of information among institutions through the site visit process; highlights best practices; and serves as a benchmark of quality. Through this process, uniform, high standards of animal care and use may be achieved under a broad range of varying national requirements because of the overarching quality assurance derived from AAALAC International’s accreditation program. Accreditation of animal care and use programs in India is a fairly new proposition, but is rapidly gaining attraction. As the biomedical research enterprise in India continues to gain momentum, so too have the merits of an international quality assurance validation system become increasingly recognized. To that end, the AAALAC International accreditation program is herewith described, including observations of findings identified during on-site assessments.